Pattern of Disability and its Relationship with Disease Related Physical Involvement, Stigma, and Mental Health Status among People Living with Leprosy - Sharma, Pawan; Bhandari, Anup Raj; Singh, Swarndeep; Gurung, Grisha; Joshi, Chunauti; Shakya, Rajesh; Amatya, Amit; Shakya, Rabi (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
Background: Leprosy continues to be a major cause of preventable disability, particularly in low-resource settings. While its physical impairments are well-documented, the relationship between disability, leprosy-related stigma, and mental health remains underexplored, especially in marginalized communities. This study aimed to assess the pattern of disability and its association with disease-related physical involvement, stigma, and mental health among people living in a leprosy colony in Nepal. Materials and Methods: A cross-sectional descriptive study was conducted among 119 residents of Khokana Arogya Ashram, a sheltered colony for people affected by leprosy. Data were collected on socio-demographic and clinical profiles, stigma (SARI Stigma Scale), mental health status (Hospital Anxiety and Depression Scale – HADS), and disability (12-item WHO Disability Assessment Schedule 2.0 – WHODAS 2.0). Non-parametric statistical tests (Spearman correlation and Mann-Whitney U-test) were used to assess associations. Results: The highest disability scores were noted in the “getting along” domain, while “mobility” had the lowest. Overall disability scores were significantly associated with age, lower education, leprosy-related ulcers, eye involvement, facial palsy, aesthetic disfigurement, and elevated HADS scores. However, there was no statistically significant association between stigma scores and disability. Conclusion: Among people affected by leprosy in a segregated community, disability was more closely associated with physical impairment and mental health symptoms than with perceived stigma. These findings emphasize the need for comprehensive care approaches that address both physical and psychological aspects of disability in leprosy.